(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
This analysis concerns the thematic and formal structure of the Rigvedic text X, 69, the hymn of the fire of Vadhryáśva. The basic structure is a sequence of pairs of stanzas, arranged in their turn in two sets of six (1-2, 3-4, 5-6 + 7-8, 9-10, 11-12), each one set with characteristics of its own but also with correspondences in particular between every pair of stanzas and the respective pair at the same height in the other ‘column’. Among these correspondences one can see the mirrored copulative syntagmas which describe the enemies of Vadhryáśva in 6b and 12c: dā́sā vr̥ trā́ṇy ā́ryā “the defenses of both Dāsas and āryas” / no ájāmīm̐ r utá vā víjāmīn “whether non-kin or another branch of our kingroup”; some considerations about the terms ā́rya- and arí- are here added. KEYWORDS: Old Indic, Rigveda, Vedic hymns, poetic structure